Perancangan Sistem Keuangan SPP Siswa Berbasis Web - Budiman, Ramdani; Suyatno, Nur Hidayanti; Kania, Raden; Solihati, Tifani Intan; Oktavia, Andini; Asrori, Khasan (Jurnal Ilmiah Sains dan Teknologi, 2025)
SMK PGRI 2 Serang City is a private educational institution until now the total number of students are 249 students, it will be inconvenient if the cost of educational facilities was still done manually using paper, namely paying tuition fees, making school financial reports such as money coming in and money out using a cash book that can easily be lost or damaged if needed at any time for the validation process between the student and the school or the process of making school financial reports every month. The system development method used is the waterfall method and using the programming language PHP and MySQL as the storage databases. The purpose of this research is to design a reporting system that can facilitate the processing of student finances, simplify the process of calculating the student financial system and simplify information systems for processing student financial data based on a website.